Anisotropic large magnetoresistance and Fermi surface topology of terbium monoantimonide. (May 2022) - Tang, F.; Shen, X.; Zhou, J.; Cong, S.; Zhang, L.; Zhou, W.; Han, Z.-D.; Qian, B.; Jiang, X.-F.; Zheng, R.-K.; Zhao, W.; Kan, X.-C.; et al.
Abstract: Rare-earth monopnictides have received a great deal of attention for their exotic magnetic and electronic properties. Here, we grow high-quality TbSb single crystals, and perform their magnetization, specific heat and transport measurements, and band structure calculations. In this compound, an antiferromagnetic phase transition emerges at ∼14.5 K ( T N ), below which metamagnetic behaviors can be observed. Specific heat data suggest that Γ4 triplet state dominates the ground magnetic properties, and thus gives rise to weak magnetic anisotropy. Analogous to other isostructural counterparts, TbSb shows extreme magnetoresistance and triangular temperature-field phase diagram. Hall resistivity measurements reveal that carrier concentrations and mobilities change their values in different magnetic states. These findings are supported by the theoretical calculations from which the effect of magnetic orderings on Fermi surface topology can be determined. Nevertheless, the magnetoresistance below and above T N in TbSb shares similar angle dependences, and follows the fashions as observed in those nonmagnetic sister compounds because of its weak anisotropy in magnetization. Our studies uncover the spin ordering effects on angular magnetoresistance and electronic band structures of TbSb, and could be employed to understand the related issues in other systems with similar magnetic behaviors. Graphical abstract: Image 1 Highlights: TbSb is an antiferromagnetic semimetal, and shows weak magnetic anisotropy and extreme magnetoresistance with a triangular temperature-field diagram as observed in those nonmagnetic sister members. The temperature-field diagram is constructed by plotting T m and T i as a function of magnetic field. Here, T m and T i denote the T where ∂ ρ xx /∂ T = 0 and ∂ ρ xx /∂ T takes minima, respectively. Carrier concentrations change their values in different magnetic field ranges, which yield the magnetoresistance diverging from a parabolic field dependence and implies that the electronic properties could be altered with the evolution of magnetic fields. In TbSb, spin ordering has significant effect on the Fermi surface, instead of the angular magnetoresistance.